Factors associated with complications and postoperative visual outcomes of cataract surgery; A study of 1,632 cases - Thevi Thanigasalam (Journal of Ophthalmic & Vision Research, 2015)
Purpose: Cataract surgery is the most common intraocular surgery performed all over the world and has advanced technically in recent years. As in all surgeries, complications are unavoidable. Herein we report factors associated with complications and visual outcomes of cataract surgery. Methods: This retrospective cohort study included data of 1,632 cataract surgeries performed from 2007 to 2010 which was obtained from the cataract registry of the Malaysian National Eye Database. Demographic features, ocular and systemic comorbidites, grade of surgeon expertise and duration of surgery, type of anesthesia, intraoperative and postoperative complications, and the type of intraocular lens were recorded. Best corrected visual acuities were compared before and after the operation. Results: Mean patient age was 66.9 years with equal gender distribution. The majority of subjects had age related cataracts. Phacoemulsification was done faster than other surgeries, especially by specialist surgeons. History of prior ocular surgery and operations performed under general anesthesia were associated with greater complications. Phacoemulsification was associated with less complications and better visual outcomes. The age and etiology of cataract did not affect complications. Malays, absence of ocular comorbidities, left eyes and eyes operated under local anesthesia were more likely to experience more visual improvement. Gender, age, cause of cataract, systemic comorbidities and surgeon expertise as well as intra-and postoperative complications did not affect the visual outcomes. Conclusion: Phacoemulsification had good visual outcomes in cataract surgery. Duration of surgery, expertise of the surgeon and complications did not affect the visual outcomes.